2012
DOI: 10.2478/rehab-2013-0027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kinesiology Taping method on pain reduction after rib broken – initial report

Abstract: Introduction: The rib broken are most frequent damages of chest. They cause strong pain, and make difficulties in breathing and changing position of body. Uncomplicated breakdowns are cured by analgesics drugs. One of physical methods for pain decreasing in musculoskeletal dysfunctions is kinesiotaping. The aim of this study was assessment of effectiveness Kinesiology Taping method after rib broken and their influence on pain reduction and breathing parameters. Material and methods : In this study take par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A similar study design was used by Castro-Sanchez et al [ 17 ] in their study of the effects of Kinesio taping on pain relief of the lumbar spine. The influence of the Kinesio taping method on pain control was also investigated by Czyzewski et al [ 18 ], who focused on the pain experienced after fracture of the ribs. Interesting research was also done at Hacettepe University in Ankara, Turkey in collaboration with the Shanghai Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study design was used by Castro-Sanchez et al [ 17 ] in their study of the effects of Kinesio taping on pain relief of the lumbar spine. The influence of the Kinesio taping method on pain control was also investigated by Czyzewski et al [ 18 ], who focused on the pain experienced after fracture of the ribs. Interesting research was also done at Hacettepe University in Ankara, Turkey in collaboration with the Shanghai Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The use of kinaesiotaping to support the chest wall in the presence of rib fractures has gained popularity in clinical settings over the years. Only two studies of low methodological quality and small sample sizes investigated the effect of kinaesiotaping on patients with undisplaced rib fractures (Czyzewski et al 2012 ; Sareen, Jain & Pagare 2015 ). Few experienced trauma physiotherapists (6%) reported using kinaesiotaping frequently as part of patient management following major chest trauma (Van Aswegen et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Outcome measures are used for such purposes. Table 2 displays the outcome measures that have been used in clinical trials in the blunt and penetrating trunk trauma population (Baker et al 2018 ; Czyzewski et al 2012 ; Dhillon et al 2015 ; Fagevik Olsén et al 2016 ; Grammatopoulou et al 2010 ; Sareen et al 2015 ; Schneiderman et al 2013 ; Van Aswegen et al 2010 , 2011 ; Whelan, Van Aswegen & Corner 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…KT effectiveness was confirmed in athletes experiencing pain after spinal-stress training (Garczyński et al, 2013;Merino-Marban et al, 2013). It was also shown that KT helps to reduce chronic lumbar-sacral pain (Bae et al, 2013;Castro-Sánchez et al, 2012;Lemos et al, 2014;Paolini et al, 2011) and Czyżewski et al found that KT decreases pain in the case of rib fractures and exhibits an anti-swelling properties (Czyżewski et al, 2012).…”
Section: Introductionmentioning
confidence: 95%